Regulatory role of the METTL3/MALAT1 axis in multiple myeloma progression - Xiaohong Lu; Yafei Li; Ruie Li; Jingheng Zhang; Jiayu Peng; Yan Zhang (Journal of Bone Oncology)
Objective: Methyltransferase-like 3 (METTL3) plays a crucial role in cancer progression, both in m6A modification-dependent and −independent pathways. We aimed to elucidate the mechanism by which METTL3 and the long noncoding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) contribute to the pathogenesis of multiple myeloma (MM). Methods: Bone marrow samples were collected from 56 patients with MM and 42 healthy donors, followed by assessment of METTL3 and MALAT1 levels. An interaction between METTL3 and MALAT1 was also identified. METTL3- and MALAT1-related oligonucleotides were transfected into RPMI8226 and U266 cells to explore their role in cell growth. Apoptosis, migration, proliferation, and invasion of RPMI8226 and U266 cells were assayed. Results: Elevated METTL3 and MALAT1 levels were observed in patients with MM. Interference with METTL3 or MALAT1 inhibited the malignant behavior of RPMI8226 and U266 cells. There was an interaction between METTL3 and MALAT1. Overexpression of MALAT1 reversed the inhibitory effects of METTL3 interference on tumor cell malignancy. Conclusion: METTL3 augments MM development by enhancing MALAT1 expression.